2019
DOI: 10.3389/fphys.2019.00412
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Improve Glycometabolism and Liver Regeneration in the Treatment of Post-hepatectomy Liver Failure

Abstract: Background The mortality rate of post-hepatectomy liver failure (PHLF) remains very high, and liver transplantation is the only effective treatment regimen for PHLF. Cell transplantation is a potential treatment for liver diseases. Previous studies have proved that mesenchymal stem cells (MSCs) have immunomodulatory functions. In the present study, we found that MSCs promoted glycogen synthesis and liver regeneration in the treatment of PHLF. MSC transplantation also improved the survival rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Interestingly, we observed that the MSC transplantation could significantly reduce the number of hypoglycemic events in recipients as a major life-threatening complication of T1D in children. This effect was reported in a preclinical study of MSC transplantation for posthepatectomy liver failure (61). Additionally, for the first time, we showed that early transplantation of MSCs significantly reduced the rate of grade II hypoglycemic events in T1D patients compared to late transplantation of MSCs.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, we observed that the MSC transplantation could significantly reduce the number of hypoglycemic events in recipients as a major life-threatening complication of T1D in children. This effect was reported in a preclinical study of MSC transplantation for posthepatectomy liver failure (61). Additionally, for the first time, we showed that early transplantation of MSCs significantly reduced the rate of grade II hypoglycemic events in T1D patients compared to late transplantation of MSCs.…”
Section: Discussionsupporting
confidence: 77%
“…A PHLF model was established by 90% hepatectomy in rats. This is a classic animal model to simulate PHLF based on the previous studies 19 . The levels of liver enzymes (ALT and AST) in hepatectomized rats were sharply increased.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative resveratrol administration enhanced the homing capacity of MSCs into liver tissue, thus decreasing the expression of TNF-α and IL-6 and improving liver regeneration in PH-treated rats [57]. In a 90% PH model, MSCs were proven to improve the glucose metabolism and survival rate of rats with PH-induced ALF via promotion of hepatocyte proliferation through the AKT/GSK-3β/β-catenin pathway [58]. Moreover, implantation of bioencapsulated MSCs promoted liver regeneration and increased the survival rate of 90% PH-treated rats from 21% to 91% via induction of hepatogenic differentiation and the secretion of growth factors [59].…”
Section: Msc Transplantation Promotes Liver Regeneration In Partial Hmentioning
confidence: 99%